Rancang Bangun Sistem Informasi Monitoring Pelanggaran Siswa SMP Negeri 1 Laboya Barat Berbasis Web - Apliana Kaka; Adelbertus Umbu Janga; Felysitas Ema Ose Sanga (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
The Family Welfare Empowerment (PKK) is a vital community organization with a significant role in addressing social issues. One such issue is the increasing number of juvenile delinquency cases in schools, which has become a major concern for both educational institutions and parents. Schools must be proactive in monitoring their students to address this problem effectively. However, traditional manual monitoring processes are inefficient and time-consuming. To overcome this, there is a need for an efficient, user-friendly, and multi-user monitoring system that enables both schools and parents to access information about their children's behavioral violations. This student violation monitoring system is designed to be web-based, utilizing UML (Unified Modeling Language) for system design and employing the Waterfall development method. The goal of this system is to provide an effective solution for managing and tracking student violations, allowing for better control and prevention of delinquent behavior within the school environment. By implementing this system, both school authorities and parents will be able to collaborate more effectively in monitoring and addressing student behavior.